SECURITIES MARKET AS AN INDICATOR OF INNOVATION - Victor M. Askinadze (Статистика и экономика)
The article presents a potential possibility to use stock market Indices as an indicator of emerging innovative economy. The focal point is the significance of taking into account the stock market Indices’ dynamics and volatility.